Disruption of the C5a/C5aR1 axis confers protection against hookworm infection in lung - Walachowski, Sarah; Garo, Lucien; Sharma, Arjun; Jayaraman, Archana; Noon, Jason; Reinhardt, Christoph; Bosmann, Markus (Frontiers in Immunology, 2024)
Hookworms are soil-transmitted parasitic nematodes that penetrate the host skin before migrating to the lungs. With an estimated 500-700 million people infected worldwide, hookworm infections are a neglected tropical disease and a significant cause of morbidity, particularly in children, pregnant women, and immunocompromised individuals. Although there is ample evidence that complement activation is pivotal to elicit a protective host immune response against invasive pathogens, its role in hookworm infection remains insufficiently explored. Here, we investigated the complement anaphylatoxin, C5a, during the early lung stage of infection with Nippostrongylus brasiliensis in C57BL/6J wild type and C5aR1-/- mice. Despite the previously reported ability of lung larvae to evade complement activation, C5a was detectable locally in lung tissue and bronchoalveolar lavages. Surprisingly, C5aR1 presence directly contributed to the pathogenicity of hookworm infection. The burden of viable parasites in the lungs was mitigated in C5aR1-/- mice, compared to C57BL/6J mice 48 hours post-infection. Additionally, C5aR1-/- mice showed significantly reduced lung injury, lower cytokine release, attenuated alveolar hemorrhage, and limited alveolar-capillary barrier disruption. Neutrophils were the most abundant and highest C5aR1-expressing cell type in the alveolar space after infection. Deficiency of C5aR1 reduced the influx of neutrophils, monocytes, and eosinophils to the pulmonary airways. RNA sequencing of alveolar neutrophils revealed C5aR1-dependent regulation of the novel nuclear protein, DEDD2. In conclusion, our findings highlight the impact of C5aR1 signaling in neutrophils during hookworm infection uncovering an unexpected downside of complement activation in parasitic infection.